ТИЛ ВА МАДАНИЯТ МУШТАРАКЛИГИНИНГ МЕТАФОРИК МАЪНОЛАРДА ИФОДАЛАНИШИ - Ибрагимов, Ю.М. (SCIENCE and SOCIETY, 2019)
The article deals with words, names of animals, plants, proper names expressing the metaphorical meanings of linguistic and cultural relations, mainly linguistic units that convey additional methaphoric meanings.